Perceived Barriers Before and After a 3-Month Period of Modified Ride-On Car Use. Issue 3 (July 2020) - Logan, Samuel W.; Feldner, Heather A.; Bogart, Kathleen R.; Catena, Michele A.; Hospodar, Christina M.; Raja Vora, Joseline; Smart, William D.; Massey, William V.
Abstract : Purpose: The purpose of the study is to examine how perceived barriers change before and after a 3-month period of modified ride-on car use. Methods: This study used a qualitative content analysis of perceived barriers. Fourteen caregivers (13 mothers; 1 grandmother) responded to a single-question, free-response survey before and after a 3-month period of modified ride-on car use. Results: A total of 11 and 20 perceived barriers were reported before and after the 3-month period. Environmental barriers were the most frequently reported before and after the 3-month period. Conclusions: Pediatric physical therapists need to be aware of the potential perceived barriers that families may experience in regard to young children with disabilities using modified ride-on cars and determine strategies to support families on an individual basis. Abstract : The purpose of the current study is to examine how perceived barriers change before and after a three-month period of modified ride-on car use.